Penerapan Syariat Islam: Problematika dan Wacana Solusi - Mabrur, Muhammad (Alhadharah: Jurnal Ilmu Dakwah, 2013)
In this paper the writer discusses the background of the demands for the application of Islamic law, opinions, and change of value as the results of the imposition of Islamic law in the lights of communication science. First the writer sees the background of the emergence of the demands. Then he looks at the response of some organizations in addressing these demands. The author argues that some people have different perceptions in response to the application of Islamic law. Furthermore, in the level of applications in the field the author attemps to see the possibility of the occurrence of some of the obstacles that must be addressed in a wise way. For this case the policy holder needs to anticipate and pay attention to the steps that must be taken in realizing the application of the Islamic Sharia, so that the implementation not counter-productive.